A Short Review on Membranes for Helium Separation and Purifications - Mohamad Atif, Mohamed; Norazlianie, Sazali; Fatin Nurwahda, Ahmad; Nor Hasrul Akhmal, Ngadiman; Mohd Hafiz Dzarfan, Othman (Akademi Baru, 2019)
Preponderance of membranes have Helium (He) selectivity which causes their gas separation has a potential for helium revival and purification. This review conveys the recent investigations and patent reports for membranes embarking on separation of He. This involves direct retrieval from natural gas which is an auxiliary stage in natural gas processing, alongside niche applications where helium recycling is capable. A summary of the available literatures on polymeric and inorganic membranes for helium separation is presented. In comparable gas industries, discussion on commercial gas separation membranes is with regard to their capacity for helium separation. This paper includes the assorted patented designs of helium recovery and purification by membranes from variety of sources, considering that these exhibit the viability of current available polymeric membranes to separate helium. The review particularly emphasizes processes in which membranes are utilized together with other available separation technology such as pressure swing adsorption (PSA). The combination of technology able to generate high-purity helium gas. This paper also aims to demonstrate the viability of membrane separation process for helium recovery and purification. Current process is focusing on reusing helium instead of separation from its raw sources.